A Cerebral Palsy Student’s University Reading Lived Experience - Poh Heng, Philip Wee (AJELP: Asian Journal of English Language and Pedagogy, 2017)
This article presents a transcendental phenomenological study of the indigenous meanings of the reading challenges of a student with cerebral palsy. An understanding of the phenomenon could contribute to the conversation on academic literacy support for struggling readers, including those with medical and/or physical issues.